Activating antioxidant enzymes, hyoscyamine and scopolamine biosynthesis of Hyoscyamus niger L. plants with nano-sized titanium dioxide and bulk application - Mansour GHORBANPOUR; Mehrnaz HATAMI; Mahmoud HATAMI (Acta Agriculturae Slovenica)
Application of nanotechnology is now widely distributed overall the life, especially in agricultural systems. This study intended to indicate the impacts of nano-sized titanium dioxide particles (NT) and bulk (BT) on antioxidant enzymes activities including superoxide dismutase (SOD), peroxidase (POX) and catalase (CAT), and variations of two major tropane alkaloids such as hyoscyamine (HYO) and scopolamine (SCO) in Hyoscyamus niger L. Plants were treated with different concentrations of NT and BT (0, 20, 40 and 80 mg l-1). Alkaloids extracted were identified by gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS) analysis. Results showed that SOD activity increased with increasing titanium dioxide concentration in both nano-particles and bulk treated plants. However, the highest and the lowest POX activity were observed in plants exposed to NT at 40 mg l-1 and control, respectively. Generally, all tested enzymes activities were higher in NT treated plants that those of BT except CAT activity at 80 mg l-1. The highest alkaloids content values, HYO: 0.286 g kg-1 and SCO: 0.126 g kg-1, were achieved in plants treated with NT at 80 and 20 mg l-1, respectively. The maximum and minimum plant biomass and subsequently total alkaloids yield were obtained in plants exposed to NT at 40 mg l-1 and controls, respectively. Our results suggest that NT in appropriate level (40 mg l-1) may act as an elicitor for biochemical responses and tropane alkaloids biosynthesis in H. niger plants.